Potassium channels support anion secretion in porcine vas deferens epithelial cells - Malreddy, Pradeep Reddy (Kansas State University, 2009)
Epithelial cells lining the vas deferens modify the luminal contents to which sperm are exposed in response to neuroendocrine, autocrine and lumicrine transmitters. The role and identity of vas deferens epithelial potassium channels that provide the correct luminal environment for sperm maturation and delivery have not yet been determined. Cultures of vas deferens epithelial cells isolated from adult pigs were employed to investigate contributions of selected ion channels to net flux. A two-pore potassium channel, TASK-2, was identified on the apical membrane of cultured primary porcine vas deferens epithelial cells (1°PVD). Bupivacaine, a known TASK-2 inhibitor, when added to the apical bathing solution, inhibited forskolin- stimulated short circuit current, Isc, in a concentration dependent manner with a maximum inhibition of 72 ± 6% and an IC50 of 7.4 ± 2.2 µM. Apical exposure of 1°PVD cells to quinidine, lidocaine, and clofilium (other known TASK-2 blockers) inhibited forskolin-stimulated Isc in a concentration dependent manner. Fitting a modified Michalis-Menten function to the data revealed IC50 values of 274 µM, 531 µM, and 925 µM, respectively. Riluzole, a two-pore potassium channel activator, stimulated bupivacaine-sensitive Isc, further confirming the contribution of TASK-2 to net ion flux. Western blotting demonstrated the presence of TASK-2 immunoreactivity in 1°PVD cell lysates, while immunocytochemistry demonstrated apical localization of the targeted epitope in virtually all cells lining native porcine vas deferens. These results suggest that TASK-2 likely plays a role in vas deferens epithelial ion transport that may account for the reportedly high concentration of potassium in the male reproductive duct lumen. TASK-2 likely contributes to male fertility as an integral member of the regulated transport processes that account for the luminal environment to which sperm are exposed.
Keywords: Vas deferens epithelia; TASK-2; KCNK5; Porcine; Potassium channels; Male reproductive tract; Biology, Animal Physiology (0433); Biology, Veterinary Science (0778); Biophysics, General (0786)